SKILL OF TEACHER CANDIDATES IN INTEGRATING THE CONCEPT OF SCIENCE WITH LOCAL WISDOM (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2015)
Learning science is not limited to reviewing the concepts, but strengthens the identity of a nation that has a diversity of cultures. Science learning objectives that have been set in Indonesia, including the student is able to apply the science wisely, to maintain and preserve the cultural survival. The study aims to measure students' ability to relate concepts of science with local knowledge to use mind maps compiled individually. The results showed that 85% of teacher candidates are able to determine the relationship of science and local knowledge correctly. The ability to link the two domains, through the literature review, observation and interviews.